2013
DOI: 10.1002/pi.4554
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual solvent on physical and chemical properties of amorphous glassy polymer films

Abstract: One of the most important areas of current research is the study of the influence of the prehistory of samples of amorphous glassy polymers on their physical and chemical properties. The study of structural changes by high temperature IR spectroscopy compared with of quantum chemical calculations allows for an understanding of the mechanism and nature of such processes. The changes in the structure of the polymer chain depending on the type of solvent used in the formation of the films are demonstrated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Therefore, specifically for membrane material science, the stability of gas separation properties in time and the effect of preparation technique and operation mode of the polymer membrane (film) on its gas separation characteristics are very important issues [ 1 ]. As a rule, polymer membranes are made out of polymer solutions, thus gas separation properties are sensitive to solvent type and polymer solution concentration [ 2 , 3 , 4 , 5 ], presence of residual solvent, and method of its removal [ 6 , 7 , 8 , 9 ]. Thermodynamic nonequilibrium state of glassy amorphous polymers leads to a change in nonequilibrium free volume and consequently gas separation properties of polymer membranes during exploitation due to physical aging [ 1 , 9 , 10 ] or plasticization with a separated component [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, specifically for membrane material science, the stability of gas separation properties in time and the effect of preparation technique and operation mode of the polymer membrane (film) on its gas separation characteristics are very important issues [ 1 ]. As a rule, polymer membranes are made out of polymer solutions, thus gas separation properties are sensitive to solvent type and polymer solution concentration [ 2 , 3 , 4 , 5 ], presence of residual solvent, and method of its removal [ 6 , 7 , 8 , 9 ]. Thermodynamic nonequilibrium state of glassy amorphous polymers leads to a change in nonequilibrium free volume and consequently gas separation properties of polymer membranes during exploitation due to physical aging [ 1 , 9 , 10 ] or plasticization with a separated component [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in [ 8 , 13 , 14 , 15 , 16 ], it has been shown that interaction between functional groups of polymer with a solvent with formation of hydrogen bonds leads to reorientation of these groups over the polymer backbone, changing its conformational parameters [ 13 , 14 , 15 , 16 ]. If hydrogen bond formation leads to an increase in the quantity of elementary unit conformers of the same geometry, it is appropriate to suppose ordering of conformational composition of elementary units of macromolecule, which results in chain packing ordering.…”
Section: Introductionmentioning
confidence: 99%
“…One of the rapidly developing directions of poly mer materials science is related to the problem of residual solvent [1][2][3][4][5][6][7][8][9][10][11][12]. For example, for films and membranes based on polyimides, polycarbonates, and Hyflon® fluoro containing polymers solution cast and dried to constant weights at room temper ature in air or in vacuum or for films annealed above the glass transition temperature, the effects of preparation and the thermal treatment conditions on the morphology [1] and gas separating charac teristics of films [2,3,[7][8][9] are explained by the presence of residual solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of polymer and polymer‐based nanomaterials are experimentally investigated in several of the research papers. The influence of the preparation of samples of amorphous glassy polymers on their physical and chemical properties is studied by analyzing the changes in the structure of the polymer chain as a function of the type of solvent used in the formation of the films . In another paper, the influence of hydrophilic and hydrophobic imidazolium ionic liquids on the curing kinetic, mechanical, morphological and ionic conductivity properties of nitrile rubber composites was studied, and it is proved the addition of such liquids can change the glass transition temperature .…”
mentioning
confidence: 99%